Review of Antonio D. Sison, ed., Deep Inculturation: Global Voices on Christian Faith and Indigenous Genius - Joe Evans (Journal of Moral Theology)
Review of Antonio D. Sison, ed., _Deep Inculturation: Global Voices on Christian Faith and Indigenous Genius_